Nivel de sostenibilidad en la ciudad de Quevedo, provincia Los Ríos - Bermello Alcívar, Michelle Monserrate (2023)
This research project was carried out in the urban area of Quevedo canton, Los Ríos province, with the aim of evaluating the level of environmental sustainability of the city, applying multivariate analysis for the identification of environmental variables that influence sustainable development of the canton. The methodology was exploration and analysis of background information related to the topic, which was carried out through secondary information sources extracted from the Territorial Development and Planning Plan (PDYOT), while the primary source information was the application of surveys and field observation, later 18 indicators were evaluated to determine the urban environmental sustainability of the city in question. Having as a result the current diagnosis of the Quevedo canton, which provided relevant information on social, cultural and physical interactions to determine the indicators to be evaluated; with the data obtained from the surveys the statistical technique Principal Components Analysis (PCA) was carried out that allowed to integrated and simplify those variables that could have significant structures, with this analysis it was possible to group into ten indicators: population growth rate, net population density, percentages of multifamily residential areas, balance between tertiary activities and residences, built area per inhabitant, age of buildings, buildings hardness, patrimonial buildings, housing density, green areas per inhabitant, green roofs, proximity of green areas and public spaces, wastewater consumption per contribution, electricity consumption, drinking water consumption, fire risk and risk of flooding; in addition, a decision tree was made where the predictive sustainability variable was identified, the dependent variable used was “Built area per inhabitant” since it was the best fit and correlation in the communalities table. Through the results presented, strategies and objectives were proposed for each variable and indicator of greater relevance to improve the city, through constructive regulations in protected areas and including the promotion of environmental education and the efficient use of natural resources in order to optimize the way of operating, administering and maintaining a sustainable city. Keywords: Urban Sustainability, Environmental Diagnosis, Urban Strategies, Sustainable City Model, Quality of Life.